2018
DOI: 10.1186/s13046-018-1005-y
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide reverses the chemoresistance in hepatocellular carcinoma: a targeted intervention of 14–3-3η/NF-κB feedback loop

Abstract: BackgroundMulti-drug resistance (MDR) is one of the main obstacles for treatment of advanced/recurrent hepatocellular carcinoma (HCC). We have previously identified arsenic trioxide (ATO) as an effective metastasis/angiogenesis inhibitor in HCC. Here, we further found that MDR-HCC cells were more sensitive to ATO.MethodsThe MDR-HCC cells were used as experimental models. Biological functions were investigated using cell transfection, polymerase chain reaction, western blot, southwestern blot, immunostaining, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 47 publications
2
27
0
1
Order By: Relevance
“…The regulation of noncoding RNAs, such as miR-125 [32], miR-31 [34], H19 [35], and NR2F1 [36], has been shown to be involved in the development and progression of HCC and is involved in tumor resistance. The NF-κB, PI3K/Akt, GSK3β/β-catenin and HIF-1α signaling pathways have been reported to be involved in HCC chemoresistance [37][38][39][40]. In our study, as shown in Fig.…”
Section: Rbm8a (Y 14)supporting
confidence: 52%
“…The regulation of noncoding RNAs, such as miR-125 [32], miR-31 [34], H19 [35], and NR2F1 [36], has been shown to be involved in the development and progression of HCC and is involved in tumor resistance. The NF-κB, PI3K/Akt, GSK3β/β-catenin and HIF-1α signaling pathways have been reported to be involved in HCC chemoresistance [37][38][39][40]. In our study, as shown in Fig.…”
Section: Rbm8a (Y 14)supporting
confidence: 52%
“…According to our previous researches, 14-3-3η isoform was a novel characteristic neoplastic factor in HCC, inducing the growth/ angiogenesis and MDR properties 15,16 . Moreover, by inhibiting 14-3-3 η, ATO reversed the MDR in HCC cells 11 . However, it is still uninvestigated that whether there are isoforms of 14-3-3 family could function with ATO and enhance the chemotherapeutic efficiency in CCA.…”
Section: Introductionmentioning
confidence: 95%
“…Meanwhile, ATO is also used to suppressing the progression of many solid tumors, such as breast and liver 8 . We previous revealed that ATO could effectively attenuated the growth/angiogenesis, metastasis, self-renewal, and multidrug resistance via epigenetic modification, regulation of related molecules and chemokines in HCC cells [9][10][11][12] . Nevertheless, the roles of ATO in regulating chemotherapeutic efficiency of CCA, and the potential mechanisms involved in, remains uninvestigated.…”
Section: Introductionmentioning
confidence: 99%
“…Then the protein-antibody complexes were incubated with IgG sepharose beads (Beyotime) at 4˚C for another 12 h. After then, the supernatants were removed (positive control) and the beads were washed for three times (residual supernatants, served as a negative control), boiled to remove the beads, centrifugation, and then dissolved the tested substance in water for high-performance liquid chromatography/mass spectrometry (HPLC/MS) analysis, using the Thermo Fisher Q Exactive Plus LC-MS system with the CaA standard as positive control. For the determination of protein ubiquitination, a co-immunoprecipitation assay was performed as described previously [16]. Brie y, HuH7 SR cells were treated, extracted, and the immunoprecipitation complex was prepared as described above.…”
Section: Biological Functional Analysismentioning
confidence: 99%